RANCANG BANGUN SISTEM PEMANENAN ENERGI TERBARUKAN OFF-GRID MENGGUNAKAN PANEL SURYA DAN PIKOHIDRO - Akhiriyanto, Novan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The irrigation system in several Blora Regency agricultural areas already has water wells using water pump in the middle of farming fields, so it requires electricity through the grid (PLN) which is distributed through long cables from closest residents. To solve this problem, it requires an off-grid energy system outside the grid. The objective of proposed research is how to design a hybrid off-grid energy harvesting system based on solar PV generation and picohydro, especially picohydro performance as compensating energy generated from potential energy accumulated in water storage.In this study, the aim is to utilize the picohydro device so that it is able to generate the energy of the water flow from the water tank outlet to fresh water users. So that the energy of water flow can optimally drive small turbines in picohydro, significant parameters that affect the voltage generated by picohydro are the water level in the tank. The highest voltage generated by picohydro in the system prototype is 9.4 Volts. In general, the prototype have been completed and implemented, but still requires DC-DC converter device for charging from picohydro to the battery in 12V.